Extending the supply chain visibility boundary: utilizing stakeholders for identifying supply chain sustainability risks - Busse, Christian; Schleper, Martin C.; Weilenmann, Jenny; Wagner, Stephan M. (Emerald Publishing, 2017)
Purpose – The purpose of this paper is to investigate how buying firms facing low supply chain visibility can utilize their stakeholder network to identify salient supply chain sustainability risks (SCSR). Design/methodology/approach – The study employs a design science approach to develop a procedural model for identifying SCSR as a new artifact. A small-scale field-testing study in a food supply chain of a Swiss retail firm demonstrates its applicability and pragmatic validity. Findings – When stakeholder knowledge external to the supply chain is regarded as a valuable resource, a generic understanding of a buying firm’s supply chain suffices to identify SCSR hotspots without creating complexity for the SCSR management. Research limitations/implications – The paper contributes to the study of SCSR by identifying mechanisms buying firms can employ to identify SCSR hotspots and fostering the nascent understanding of responsibility attribution by stakeholders. Moreover, the emerging theory of the supply chain is enriched by paving a way to extend the supply chain visibility boundary. The procedural model is presumably most useful in contexts of elevated stakeholder pressure and low supply chain visibility. Future research should seek to validate and improve the effectiveness of the newly designed artifact. Practical implications – The procedural model is directly applicable in corporate practice to the identification of SCSR. Moreover, its application fosters the understanding of a firm’s supply chain and its stakeholder network.originality/value – SCSR is an increasingly important phenomenon in corporate practice that has received only scarce research attention. The design science approach represents a valuable means for generating theoretical insights and emergent solutions to the real-world problem of SCSR identification.